Whole genome doubling-induced the enrichment of H3K27me3 in genes carrying specific TEs in Aegilops tauschii - Guo, Hongwei; Zhang, Guoyan; Zhou, Min; Wan, Min; Zhu, Bo; Yang, Zujun; Zeng, Deying; Zeng, Zixian (Frontiers in Genetics, 2023)
Polyploidization plays important roles in the evolution and breeding of the common wheat. Aegilops tauschii, the D-genome progenitor of the common wheat, provides a valuable pool of resistance genes to multiple diseases. Extensive studies focus on the exploration of these genes for wheat improvement. However, few studies have unveiled alternations on genome-wide expression pattern and histone modifications induced by whole-genome doubling (WGD) process. In this study, we conducted transcriptome analysis for the diploid and tetraploid Ae. taushcii lines using the leaf and root tissues. Both lines tend to display similar tissue-specific pattern. Interestingly, we found that TEs located in genic regions were depleted of the repressive histone mark H3K27me3, whereas their adjacent chromatin was enriched with H3K27me3. The tetraploid line exhibited higher levels of H3K27me3 in those regions than the diploid line, particularly for genic regions associated with TEs of the long interspersed nuclear elements (LINEs), CACTA, PIF/Harbinger, Tc1/Mariner and unclassed DNA transposon. Surprisingly, the expression levels of these TEs cognate genes were negatively associated with the levels of H3K27me3 between the tetraploid and diploid lines, suggesting the five types of TEs located within genic regions might be involved in the regulation of the ploidy-related gene expression, possibly through differential enrichment of H3K27me3 in the genic regions. These findings will help to understand the potential role of specific types of TEs on transcription in response to WGD.